Clinical, Demographic, and Criminal Behavior Characteristics of Patients With Intellectual Disabilities in a Canadian Forensic Program - Ray, Ipsita; Simpson, Alexander I. F.; Jones, Roland M.; Shatokhina, Kristina; Thakur, Anupam; Mulsant, Benoit H. (Frontiers in Psychiatry, 2019)
Background: People with Neurodevelopmental Disorders (NDD) Intellectual Disability (ID), Autism-Spectrum Disorder (ASD) -- and forensic issues constitute a challenging clinical group that has been understudied in forensic settings. Methods: We assessed the characteristics of patients with NDD under the authority of the Ontario Review Board (ORB) in a large forensic program of a tertiary psychiatric hospital (excluding those with a cognitive disorder) and compared their characteristics with those of a non-NDD control group. Results: Among 510 adult ORB patients, 50 had a NDD diagnosis. NDD patients were: younger; with a lower level of education; less likely to have been married or employed, less likely to have a diagnosis of psychosis, less likely to be ‘not criminally responsible’; more likely to have committed a sexual offence, more likely to have a diagnosis of paraphilia, and more likely to be ‘unfit to stand trial’. They were also more likely to be treated in a secure unit, to have conflicts with co-patients, or to be involved in physical or verbal assault incidents. Conclusion: Our findings have major implications for clinicians, clinical leaders, and policymakers about the specific needs of patients with NDD presenting with forensic issues. In particular, their higher level of conflict suggests a need for higher levels of, or different, clinical support and risk management.